Novel node upgradation strategy for migration to elastic optical networks - Xiaodong FU; Yongcheng LI; Gangxiang SHEN (Tongxin xuebao)
For migration from dense wavelength division multiplexing (DWDM) networks to elastic optical networks (EON),it is required to upgrade the traditional reconfigurable optical add-drop multiplexer (ROADM) to the new-generation ROADM that supports flexible grids.However,for a large-scale optical network,it is generally impossible to upgrade the ROADM nodes all in once; rather,they would be upgraded gradually.For this,it is critical to study different strategies for selecting the ROADM nodes to be upgraded.Also,for the interconnection between different generations of ROADM,the sub-band virtual concatenation (VCAT) technique was employed to enable an optical channel to be established via traversing different types of nodes.An integer liner programming (ILP) model and an efficient heuristic algorithm were developed to jointly select the ROADM nodes to upgraded and assign spectrum resources.Simulation studies show that the proposed strategy for the upgraded node selection is efficient to perform close to the ILP model in terms of the maximum number of FS used in the whole network.